PENGARUH KOMPETENSI KERJA DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA PEGAWAI PADA PROGRAM STUDI DI LINGKUNGAN POLITEKNIK KESEHATAN TANJUNGKARANG - SRI INDRA TRI GUNARSO (Jurnal Doktor Manajemen (JDM), 2019)
The purpose of this research to knows and analyzes the influence of work competency and transformational leadership toward work satisfaction and its implication on worker performance of study program in Politeknik Kesehatan Tanjungkarang, Lampung Province. Population in this research is 297 people or all worker, whereas the sample is a number of 260 workers suitable with SEM requirement. The tool of data collection uses questioner instrument whereas the tool of data analyzing uses statistics, i.e. structural equation modeling (SEM). Based on SEM analyzing by using Lisrel 8.70, it is known that work competency variable and transformational leadership give influence toward work satisfaction of study program in Politeknik Kesehatan Tanjungkarang environment. The result describes that is very determined by work satisfaction which improve and work satisfaction is influenced by transformational leadership which applies on Study program in Politeknik Kesehatan Tanjungkarang environment.